PENDARAHAN BERULANG SETELAH 14 TAHUN PADA MALFORMASI ARTERIOVENA DI SEREBELARIS - Ni Nyoman Ayu Trisnadewi; Kumara Tini (PERDOSNI, 2018)
THE LATE ONSET RE-BLEEDING AFTER 14 YEARS OF RUPTURE CEREBELLAR AVMABSTRACTThe arteriovenous malformation (AVM), a form of abnormality in brain vascularization, in the cerebellum is a rare disorder. The risk of recurrent bleeding after initial episode at five years is very low about 3,67%. We reported a case of 25 years-old man with history of recurrent bleeding after 14 years with hydrocephalus as complication. The brain CT scan showed a bleeding in the cerebellar vermis with non-communicant hydrocephalus. The Digital Subtraction Angiography (DSA) showed a moderate left cerebellar AVM with high-flow plexiform nidus, left superior cerebellar artery as primary feeding artery with supplementary supply of the vein draining from the superior cerebellar artery to superior petrosal vein leading to the superior petrosal vein toward the contralateral transverse sinus and left sigmoid sinus. Embolization for infratentorial posterior fossa AVM bleeding needs to be considered even though previous bleeding occurs over 5 years to prevent re-bleeding.Keywords: Arteriovenous malformation, embolization, feeding artery, nidusABSTRAKKelainan pembuluh darah malformasi arteriovena (MAV) pada serebelum merupakan kelainan vaskular yang jarang terjadi. Risiko pendarahan berulang setelah tahun kelima adalah rendah sekitar 3,67%. Dilaporkan suatu kasus laki-laki, 25 tahun, dengan riwayat pendarahan serebri berulang setelah 14 tahun dengan komplikasi hidrosefalus. CT scan kepala menunjukkan adanya pendarahan pada bagian vermis dengan hidrosefalus non-komunikan. Pemeriksaan DSA (digital subtraction angiography) menunjukkan adanya MAV fosa posterior di serebelum kiri ukuran sedang dengan nidus pleksiformis high flow dan feeder utama arteri serebelaris superior kiri ke vena petrosal superior menuju ke sinus transversus kontralateral dan sinus sigmoid kiri. Tata laksana embolisasi pada MAV infratentorial fosa posterior yang mengalami pendarahan perlu dipertimbangkan walaupun pendarahan sebelumnya terjadi lebih dari 5 tahun untuk mencegah pendarahan kembali.Kata kunci: Embolisasi, feeding arteri, malformasi arteriovena, nidus